Studying the Formulation of Shallot (Allium Ascalonicum L.) Ethanol Extract Gel as Treatment of Excision Wounds in Rats - fahmi sidiq; Kamaludin Kamaludin; Rabiu H. Kankarofi (International Journal of Ethno-Sciences and Education Research, 2022)
Onion bulbs (Allium ascalonicum L.) contain alkaloid compounds and saponins which can accelerate the wound healing process. Therefore, a study was conducted on the wound healing effect of excision of ethanol extract of onion bulbs (Allium ascalonicum L.) in the form of a gel against mice (Rattus novergicus). The purpose of this research was to study the stability of the preparation as well as the effectiveness and optimum concentration in excision wound healing from the ethanolic extract of shallot (Allium ascalonicum L.) in gel dosage form. The concentration variants used were 5%, 10%, and 20%. The method used was sample extraction by maceration and wound gel was made in 3 concentrations, namely 5%, 10%, and 20% then a stability test was carried out on the preparation by cycling test method at 4⁰C and 40⁰C for 6 cycles. Besides that, gel base was also used as a negative control and octadine® gel as a positive control, then the back skin of a rat (Rattus novergicus) was injured using a surgical knife. The results of the observation of the stability of the wound gel preparation were stable both at 4⁰C and at 40⁰C. Reduction of the length of the wound at the beginning of the treatment until the wound was completely closed showed that the ethanol extract gel preparation of shallot bulbs (Allium ascalonicum L.) could reduce and heal cuts in rats with a concentration of 20% which showed the most effective wound healing effect.Onion bulbs (Allium ascalonicum L.) contain alkaloid compounds and saponins which can accelerate the wound healing process. Therefore, a study was conducted on the wound healing effect of excision of ethanol extract of onion bulbs (Allium ascalonicum L.) in the form of a gel against mice (Rattus novergicus). The purpose of this research was to study the stability of the preparation as well as the effectiveness and optimum concentration in excision wound healing from the ethanolic extract of shallot (Allium ascalonicum L.) in gel dosage form. The concentration variants used were 5%, 10%, and 20%. The method used was sample extraction by maceration and wound gel was made in 3 concentrations, namely 5%, 10%, and 20% then a stability test was carried out on the preparation by cycling test method at 4⁰C and 40⁰C for 6 cycles. Besides that, gel base was also used as a negative control and octadine® gel as a positive control, then the back skin of a rat (Rattus novergicus) was injured using a surgical knife. The results of the observation of the stability of the wound gel preparation were stable both at 4⁰C and at 40⁰C. Reduction of the length of the wound at the beginning of the treatment until the wound was completely closed showed that the ethanol extract gel preparation of shallot bulbs (Allium ascalonicum L.) could reduce and heal cuts in rats with a concentration of 20% which showed the most effective wound healing effect.